KELAYAKAN KUKU PALSU BERBAHAN LIMBAH COMPACT DISC SEBAGAI WEDDING NAIL ART (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstract. CD (Compact Disc) waste is often found in the surrounding environment with the good physical condition but can no longer be used according to its original function, causing a buildup of CD waste. CD waste in this study is to reduce the amount of CD waste in the surrounding environment by utilizing it in beauty products, namely wedding nail art. Research objectives (1) To determine the validity of artificial nail products made from CD (Compact Disc) waste. (2) to determine the feasibility of artificial nail products made from CD (Compact Disc) waste as Wedding Nail Art. This research uses an experimental method with a one-shot case study experimental design. The object of this research is fake nails made from CD (Compact Disc) waste as Wedding Nail Art. The subjects of this study have consisted of 3 validators and 15 moderately trained panelists. The Data collection techniques use observation and documentation. Data analysis used descriptive percentages. The results of the descriptive analysis showed that the fake nail products were declared valid by 3 validators based on the assessment of the indicators of strength, shape, size, and ease of application of fake nails by obtaining an average value of 71.6%. The Fake nail products made from CD (Compact Disc) waste as Wedding Nail Art have been declared eligible by 3 expert panelists on sensory tests based on indicators of color assessment, neatness, suitability of design, and final results. False nails with an oval shape got a score of 84.9%, a square shape got a score of 81.65%, a round shape got a score of 81.65%. Fake nails made from CD (Compact Disc) waste as Wedding Nail Art declared to like the results of the preference test by 15 moderately trained panelists based on indicators for assessing color, neatness, suitability of design, and final results. False nails with an oval shape got a score of 91.6%, a square shape got a score of 92.65%, a round shape got a score of 90.95%. Suggestions in this study are that the manufacture of fake nails made from CD (Compact Disc) waste requires precision to shape and bend fake nails to match the shape of the original nail and be comfortable when used. Keywords: compact disc waste, fake nails, wedding nail art. Abstrak. Limbah CD (Compact Disc) sering ditemukan dilingkungan sekitar dengan kondisi fisik masih bagus tetapi sudah tidak dapat digunakan sesuai fungsi aslinya sehingga menimbulkan penumpukan limbah CD. Limbah CD dalam penelitian ini untuk mengurangi jumlah limbah CD yang ada dilingkungan sekitar dengan memanfaatkannya menjadi produk kecantikan, yaitu wedding nail art.. Tujuan penelitian : (1) Untuk mengetahui validitas produk kuku palsu berbahan limbah CD (Compact Disc) (2) untuk mengetahui kelayakan produk kuku palsu berbahan limbah CD (Compact Disc) sebagai Wedding Nail Art. Penelitian ini menggunakan metode eksperimen dengan desain eksperimen one-shot case study. Objek penelitian ini adalah kuku palsu berbahan limbah CD (Compact Disc) sebagai Wedding Nail Art. Subjek penelitian ini terdiri dari 3 validator dan 15 panelis agak terlatih. Teknik pengumpulan data menggunakan observasi dan dokumentasi. Analisis data menggunakan deskripstif persentase. Hasil analisis deskriptif menunjukkan bahwa produk kuku palsu dinyatakan valid oleh 3 validator berdasarkan penilaian indikator kekuatan, bentuk, ukuran, dan kemudahan aplikasi kuku palsu dengan memperoleh nilai rata-rata 71,6% . Produk kuku palsu berbahan limbah CD (Compact Disc) sebagai Wedding Nail Art telah dinyatakan layak oleh 3 panelis ahli pada uji inderawi berdasarkan indikator penilaian warna, kerapian, kesesuaian desain dan hasil akhir. Kuku palsu bentuk oval memperoleh nilai 84,9%, bentuk kotak (square) memperoleh nilai 81,65%, bentuk bulat (round) memperoleh nilai 81,65%. Kuku palsu berbahan limbah CD (Compact Disc) sebagai Wedding Nail Art dinyatakan sangat suka pada hasil uji kesukaan oleh 15 panelis agak terlatih berdasarkan indikator penilaian warna, kerapian, kesesuaian desain dan hasil akhir. Kuku palsu bentuk oval memperoleh nilai 91,6%, bentuk kotak (square) memperoleh nilai 92,65%, bentuk bulat (round) memperoleh nilai 90,95%. Saran dalam penelitian ini adalah pembuatan kuku palsu berbahan limbah CD (Compact Disc) diperlukan ketelitian untuk membentuk dan melengkungkan kuku palsu agar sesuai dengan bentuk kuku asli dan nyaman ketika digunakan. Kata kunci: limbah compact disc, kuku palsu, wedding nail art.